Adult intussusception: unusual cause - A. C., Senthil Kumar; M., Malar Vannan (International Surgery Journal, 2017)
Adult intussusception is a rare entity which accounts for 1-5% of intestinal obstructions in adults and just 5% of all cases of intussusception. The basic pathology and management of intussusception in adults differs from paediatric intussusception. Here we present an interesting case of adult intussusception with an unusual cause. A 33-year-old female presented with features of intestinal obstruction. Colonoscopy was done outside our institution which reported a smooth polypoidal mass in the terminal ileum, biopsy report was pending at that time. CT abdomen revealed dilated small bowel with narrowing in the ileo caecal junction. We proceeded with laparotomy. Intraoperatively dilated ileum with intussusception of the ileocecal junction into the ascending colon was found. Right hemicolectomy with ileotransverse colon anastomosis was done. Histopathology revealed Polyp with intussusception, 5cm from ileocecal junction, with sheets of lymphoid cells showing moderate pleomorphism, infiltrating submucosa, muscularis propria, and serosa, margins uninvolved with lymph node- 3/32 positivity. Immunohistochemistry suggested B- cell lymphoma with CD20 positivity and Bcl 2 focal positivity. Routine treatment of Lymphoma after confirming with biopsy have been Chemotherapy. Role of surgeon in lymphoma is presently limited to biopsy, but there are situations like obstruction and perforation, where surgeon should take the lead role